Green Schoolyards as Outdoor Learning Environments: Barriers and Solutions as Experienced by Primary School Teachers - van Dijk-Wesselius, Janke E.; van den Berg, Agnes E.; Maas, Jolanda; Hovinga, Dieuwke (Frontiers in Psychology, 2020)
With a growing number of primary schools around the globe greening their schoolyards, opportunities arise to realize outdoor learning in natural areas on the schools premises. Despite their promising potential, green schoolyards as outdoor learning environments remain mostly unintegrated in teachers´ educational practices. In the current study, teachers of five primary schools in The Netherlands were followed for two consecutive years during a participatory action research project. Based on their experiences in this project, teachers identified barriers when integrating the green schoolyard as a learning environment and found practice-based solutions to overcome these barriers. Across schools, a total of 20 meetings were organized and 75 teachers participated in the project. Results revealed four broad themes encompassing barriers and solutions. Teachers feel hindered by outdoor learning having no formal status in their current educational practice, experience barriers related to a lack of confidence in their own outdoor teaching expertise, find it difficult to get started, and experience barriers related to physical constraints. Teachers, professionals and researchers together found solutions to overcome each specific barrier. These solutions can be translated to general recommendations: just do it, get educated and inspired, engage in real-life experiences, get an outdoor pedagogical mindset and follow a tailored process. The findings can be used by primary schools and other institutions to develop interventions that support teachers to further integrate the green schoolyard as a learning environment.